2018
DOI: 10.1111/asj.13048
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of the effects of outside temperature on farrowing rate in gilts and sows by using a multivariate logistic regression model

Abstract: It is well known that pigs are sensitive to heat stress, but few studies have assessed the critical temperature that affects farrowing rate. Therefore, the objective of the present study was to assess the effects of outside temperature on farrowing rate by using a multivariate logistic regression model. Data were obtained from 25 commercial farms, including 26,128 service records for gilts and 120,655 service records for sows. Two variables, maximum temperature (MAX) and temperature humidity index (THI), were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Farrowing rate affects herd reproductive efficiency and was reportedly associated with various factors such as parity, outside temperature, breed, and health status (Furutani et al, 2018;Koketsu et al, 2017;Sasaki et al, 2014Sasaki et al, , 2018. Additionally, no significant change was found in growth performance; this might be simply due to large performance variation among farms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Farrowing rate affects herd reproductive efficiency and was reportedly associated with various factors such as parity, outside temperature, breed, and health status (Furutani et al, 2018;Koketsu et al, 2017;Sasaki et al, 2014Sasaki et al, , 2018. Additionally, no significant change was found in growth performance; this might be simply due to large performance variation among farms.…”
Section: Discussionmentioning
confidence: 99%
“…Farrowing rate over the 5 years remained high at approximately 86% and there would be little opportunity to improve because of low heritability reporting 0.03 (Bloemhof et al., 2012). Farrowing rate affects herd reproductive efficiency and was reportedly associated with various factors such as parity, outside temperature, breed, and health status (Furutani et al., 2018; Koketsu et al., 2017; Sasaki et al., 2014, 2018). Additionally, no significant change was found in growth performance; this might be simply due to large performance variation among farms.…”
Section: Discussionmentioning
confidence: 99%
“…(2013) showed the utility of daily maximum temperature from weather stations as a heat stress indicator for farrowing rate and total number born on 16 farms in Spain and Portugal. Using public meteorological data, other studies reported the results of epidemiological investigations of total number born, weaning-to-first-mating interval, adjusted 21-day litter weight, peripartum pig deaths, and farrowing rates of gilts and sows (mainly crossbred) reared in Japanese commercial farms, in terms of herd management (e.g., Iida and Koketsu 2013; Iida and Koketsu 2014a; Iida and Koketsu 2014b; Sasaki et al . 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies used information on daily maximum temperature to investigate the effect of ambient temperature on reproductive traits of pig (e.g., Lewis and Bunter 2011; Bloemhof et al . 2013; Iida and Koketsu 2013; Iida and Koketsu 2014a; Iida and Koketsu 2014b; Sasaki et al . 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The respiratory rates and rectal and skin surface temperatures of sows in different environments were analyzed. Yosuke et al [ 27 ] also studied the effects of THI2 and maximum temperature on the farrowing rate of sows. Mellado et al [ 28 ] used THI2 to analyze the relationship between THI2 and the reproductive performance of sows.…”
Section: Introductionmentioning
confidence: 99%